Analysis of Character Education in Cases of Student Violence Against Teachers - Muhammad Fayiz Ardyansyah; Fajrian Aminuddin; Fardan Harish Nafiadi (Aslama: Journal of Islamic Studies, 2026)
This study aims to analyze the causes, forms, and strategies for addressing student violence against teachers from a character education perspective. The research method used is a qualitative approach with data collection techniques through interviews, observations, and documentation studies of teachers, school staff, and students involved in cases of violence. The results of the study indicate that the main factors influencing the occurrence of violence include family dysfunction, negative social environments, lack of religious guidance, and weak moral literacy in schools. The forms of violence found include physical and verbal violence rooted in a loss of respect and empathy for teachers. The implementation of comprehensive, integrative, and sustainable character education is key to preventing similar cases. The recommended strategies include strengthening religious values, applying positive discipline, instilling moral habits, and active collaboration between schools, parents, and the community. This study emphasizes that the revitalization of contextual character education based on human values is necessary to restore the function of schools as places for the formation of noble character and respect for teachers. The findings show that student violence against teachers is influenced by family dysfunction, negative peer environments, and weak character education. The forms of violence identified include verbal and physical aggression. The study also found that effective prevention can be achieved through strengthening religious values, implementing positive discipline, and enhancing cooperation between schools and parents.